2011
DOI: 10.1172/jci58577
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic AMPK β1 reduces mouse adipose tissue macrophage inflammation and insulin resistance in obesity

Abstract: Individuals who are obese are frequently insulin resistant, putting them at increased risk of developing type 2 diabetes and its associated adverse health conditions. The accumulation in adipose tissue of macrophages in an inflammatory state is a hallmark of obesity-induced insulin resistance. Here, we reveal a role for AMPK β1 in protecting macrophages from inflammation under high lipid exposure. Genetic deletion of the AMPK β1 subunit in mice (referred to herein as β1 -/-mice) reduced macrophage AMPK activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
328
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 307 publications
(350 citation statements)
references
References 70 publications
17
328
1
4
Order By: Relevance
“…AMPKα1 plays an important role in the suppression of proinflammatory responses and macrophage inflammatory polarisation [21,22]. Accompanied by improvements in insulin resistance and ATM inflammation, mice in the HFD + LU10 and HFD + LU20 groups also showed increased EAT AMPKα1 signalling (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…AMPKα1 plays an important role in the suppression of proinflammatory responses and macrophage inflammatory polarisation [21,22]. Accompanied by improvements in insulin resistance and ATM inflammation, mice in the HFD + LU10 and HFD + LU20 groups also showed increased EAT AMPKα1 signalling (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The catalytic subunit AMPKα1 is mainly expressed in macrophages and suppresses associated proinflammatory responses and polarisation [21,22]. Previous studies have reported that LU can enhance the phosphorylation of AMPK in HepG2 cells [23] and 3T3-L1 adipocytes [24].…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have reported the anti-inflammatory phenotype of AMPK-activated macrophages (18,29,30) with the notion that IL-4-induced polarization is attenuated in AMPK␣1-deficient murine macrophages (19). In human macrophages, AMPK activation does not generally seem to affect IL-4-induced gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…For mRNA analysis, tissues were lysed in TRIzol reagent (Life Technologies) and RNA was extracted for qRT‐PCR and mRNA assessed as described (Galic et al ., 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The AMPK β1 isoform plays a vital role in regulating AMPK heterotrimer formation and enzyme activity in mouse liver and hematological cells such as macrophages and T cells where it increases fatty acid oxidation, suppresses fatty acid synthesis, and inhibits inflammatory pathways (Blagih et al ., 2015; Dzamko et al ., 2010; Fullerton et al ., 2015; Galic et al ., 2011). It is also the primary subunit which is targeted by small‐molecule direct AMPK activators such as A769662 (Cool et al ., 2006; Sanders et al ., 2007; Scott et al ., 2014), MT‐63‐78 (Zadra et al ., 2014), and salicylate (Hawley et al ., 2012), all of which have been shown to reduce cancer cell proliferation in some (Huang et al ., 2008; O'Brien et al ., 2015; Zadra et al ., 2014), but not all studies (Vincent et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%